The iceberg drift study near Severnaya Zemlya in the spring of 2018 by remote sensing data - I. Bychkova A.; V. Smirnov G.; И. Бычкова А.; В. Смирнов Г. (Ice and Snow, 2019)
The movement of icebergs in the Laptev Sea off the coast of the Severnaya Zemlya archipelago in spring of 2018 was analyzed using satellite observations in visible spectral band. As is shown in the article the data of radiometers installed on the Landsat-8 and Sentinel-2 satellites allow monitoring of iceberg drifting in spring period in the above Arctic region. Thus, in March-April 2018, the total amount of icebergs detected near the archipelago was 4917. 4161 icebergs were in the landfast ice, 722 ones were drifting with the ice fields, and the other 32 were aground in ice fields. The average length of the icebergs was equal to 88 m; the largest of the recognized icebergs was located in the landfast ice near the ice shelf of the Matusevich fjord and it was 1240 m in length. The maximum speed of drift of the icebergs, as determined by the satellite data, was equal to 29.5 km/day. This was estimated for the situation when the speed of the near-water (surface) wind reached 20 m/s and larger. The purpose of the work was to study drifting of icebergs in order to define more exactly dynamics of the iceberg movement in this poorly known area of the Arctic. It is found that in a case of the consolidated ice cover the drift speed of ice fields with the icebergs involved depends on the driving wind force and direction. According to mean speeds of movement all icebergs were separated into three groups: the icebergs of the coastal zone with velocities smaller 1 km/day; the icebergs of the transition zone at speeds of 1.3 to 1.6 km/day; and the icebergs of the transit zone with speeds larger 2 km/day. The characteristics of the iceberg drifts obtained on the basis of daily satellite monitoring can be used in regional iceberg drift models to ensure safe economic activity on the Arctic shelf. Also, they can find application in engineering calculations in the design of infrastructure facilities on the shelf of the Arctic seas. Обсуждаются результаты спутникового мониторинга айсбергов, находившихся в сплочённом ледяном ...